Failure of Traditional Risk Factors to Adequately Predict Cardiovascular Events in Older Populations. Issue 4 (20th January 2020) - Dalton, Jarrod E.; Rothberg, Michael B.; Dawson, Neal V.; Krieger, Nikolas I.; Zidar, David A.; Perzynski, Adam T.
Abstract : BACKGROUND: Accurate assessment of atherosclerotic cardiovascular disease (ASCVD) risk across heterogeneous populations is needed for effective primary prevention. Little is known about the performance of standard cardiovascular risk factors in older adults. OBJECTIVE: To evaluate the performance of the American College of Cardiology/American Heart Association Pooled Cohort Equations (PCE) risk model, as well as the underlying cardiovascular risk factors, among adults older than 65 years. DESIGN AND SETTING: Retrospective cohort derived from a regional referral system's electronic medical records. PARTICIPANTS: A total of 25 349 patients who were 65 years or older at study baseline (date of the first outpatient lipid panel taken between 2007 and 2010). MEASUREMENTS: Exposures of interest were traditional cardiovascular risk factors, as defined by inclusion in the PCE model. The primary outcome was major ASCVD events, defined as a composite of myocardial infarctions, stroke, and cardiovascular death. RESULTS: The PCE and internally estimated models produced similar risk distributions for white men aged 65 to 74 years. For all other groups, PCE predictions were generally lower than those of the internal models, particularly for African Americans. Discrimination of the PCE was poor for all age groups, with concordance index (95% confidence interval) estimates of 0.62 (0.60‐0.64), 0.56 (0.54‐0.57), and 0.52 (0.49‐0.54) among patients aged 65 to 74, 75 to 84, and 85 years and older, respectively. Reestimating relationships within these age groups resulted in better calibration but negligible improvements in discrimination. Blood pressure, total cholesterol, and diabetes either were not associated at all or had inverse associations in the older age groups. CONCLUSION: Traditional clinical risk factors for cardiovascular disease failed to accurately characterize risk in a contemporary population of Medicare‐aged patients. Among those aged 85 years and older, some traditional risk factors were not associated with ASCVD events. Better risk models are needed to appropriately inform treatment decision making for the growing population of older adults. J Am Geriatr Soc 68:754–761, 2020